Phenotypic and Molecular Characterization of Brucella microti-Like Bacteria From a Domestic Marsh Frog (Pelophylax ridibundus) - Jaý, Maryne; Girault, Guillaume; Perrot, Ludivine; Taunay, Benoit; Vuilmet, Thomas; Rossignol, Frédérique; Pitel, Pierre-Hugues; Picard, Elodie; Ponsart, Claire; Mick, Virginie (Frontiers in Veterinary Science, 2018)
Several Brucella isolates have been described in wild-caught and “exotic” amphibians from various continents and identified as B. inopinata-like strains. On the basis of epidemiological investigations conducted in June 2017 in France in a farm producing domestic frogs (Pelophylax ridibundus) for human consumption of frog's legs, potentially pathogenic bacteria were isolated from adults showing lesions (joint and subcutaneous abscesses). The bacteria were initially misidentified as Ochrobactrum anthropi using a commercial identification system, prior to being identified as Brucella spp. by MALDI-TOF assay. Classical phenotypic identification confirmed the Brucella genus, but did not make it possible to conclude unequivocally on species determination. Conventional and innovative bacteriological and molecular methods concluded that the investigated strain was very close to B. microti species, and not B. inopinata-like strains, as expected. The methods included growth kinetic, antimicrobial susceptibility testing, RT-PCR, Bruce-Ladder, Suis-Ladder, RFLP-PCR, AMOS-ERY, MLVA-16, the ectoine system, 16S rRNA and recA sequence analyses, the LPS pattern, in silico MLST-21, comparative whole-genome analyses (including average nucleotide identity ANI and whole-genome SNP analysis) and HRM-PCR assays. Minor polyphasic discrepancies, especially phage lysis and A-dominant agglutination patterns, as well as, small molecular divergences suggest the investigated strain should be considered a B. microti-like strain, raising concerns about its environmental persistence and unknown animal pathogenic and zoonotic potential as for other B. microti strains described to date.